Fisheries and trophic structure of a large tropical river under impoundment. (June 2020) - Lima, Maria A.L.; Doria, Carolina R.; Carvalho, Adriana R.; Angelini, Ronaldo
Highlights: In the next years damming could affect more than a hundred river in Amazonian region. Damming on Madeira River changed the food web structure. The direct and indirect trophic interactions were largely modified after damming. Trophic Impact Matrix is a useful indicator to demonstrate overall impact on aquatic ecosystems. Abstract: Impacts on tropical rivers affect biodiversity and ecosystem services negatively impacting many economic activities, such as small-scale fisheries. Ecosystem-based fisheries management (EBFM) has been applied to maintain ecosystem flows and services for fisheries, to support social and economic sustainability. The suitable employment of the EBFM approach requires the understanding of the ecosystem by quantifying the trophic interactions and simulating environmental and fishery alterations. In this paper, to evaluate the early changes resulting from damming for hydroelectric power generation on the Madeira River food web, we compared two Ecopath models: before (pre) and after (post) the dam construction in November 2011. We analyzed the changes using several ecosystem attributes: fish biomass, catches, exchange of matter/energy, transfer efficiency, and, especially, the potential direct and indirect relationships among species. We also carried out simulations of the increase in the catches of several stocks in the models. Our analysis allowed us to identify several differences between before (2010–2011) and post (2012–2013) periods: an increasing of the ecosystem's respiration and consumption, a reducing of net production, transfer efficiency among Trophic Levels (TL), and total biomass of fish species by half. There was also an exchange of key species that were previously mostly non-fish compartments and became top predator fish, including B. rousseauxii, which was considered a key species in both periods. Fish species with an intermediate TL had their biomass reduced via top-down control, especially because of the increased biomass of non-migratory top predators ( Hoplias malabaricus and Plagioscion squamosissimus ). Noticeably, damming clearly reversed possible impact linkage among species, since one-third of indirect and almost one-half of direct (trophic) relations changed of signal, leading to unexpected turns in the system. Also, simulation revealed that increasing in catches strongly impact on fish biomass in the post-dam model more than in the pre-dam model. The ecosystem context of these results and the fact that they are pioneers in assess Amazonian damming can help the local managers and government to understand the impoundment effects and simulate changes in catches to foresee future impacts of reservoirs on Amazon.